Penggunaan Hypnotherapy Teknik Self – Healing Pada Ibu Hamil Resiko Tinggi Terhadap Kecemasan di Wilayah Kerja Puskesmas Kertosari Banyuwangi - Miftahul Hakiki; Indah Kurniawati; Wahyu Fuji Hariani; Indah Christiana; Nurul Eko Widyastuti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
High-risk pregnancy is a condition that can affect the condition of the mother and fetus in the pregnancy at hand, in the Kertosari Puskesmas work area there are many cases of pregnant women with high risk, including: anaemia. Pregnancy is too young, the mother is too old to get pregnant, the distance of pregnancy is too close, pregnancy is more than 3 children, HB is too high during pregnancy, this pregnancy risk condition can cause anxiety during pregnancy. Self-healing technique is a process of treatment or healing that is done by oneself through a process that is believed by oneself and also supported by the environment and external factors that support it. This self-healing can be done according to the things that the mother likes. This community service is carried out by providing training to cadre mothers which is carried out by pre and post test methods. Women cadres who have attended training on self-healing techniques have good knowledge and it is hoped that women cadres can assist pregnant women with high risk by using hypnotherapy self-healing techniques in dealing with anxiety during the pregnancy process.